2015
DOI: 10.1073/pnas.1423849112
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein CIII links islet insulin resistance to β-cell failure in diabetes

Abstract: Insulin resistance and β-cell failure are the major defects in type 2 diabetes mellitus. However, the molecular mechanisms linking these two defects remain unknown. Elevated levels of apolipoprotein CIII (apoCIII) are associated not only with insulin resistance but also with cardiovascular disorders and inflammation. We now demonstrate that local apoCIII production is connected to pancreatic islet insulin resistance and β-cell failure. An increase in islet apoCIII causes promotion of a local inflammatory milie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
106
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 42 publications
2
106
1
Order By: Relevance
“…Our studies are at variance with Avall et al (51), who reported that adenovirus-mediated ectopic ApoC3 production resulted in beta cell apoptosis and dysfunction in MIN6 cells and islets. However, the physiological significance of this study is uncertain, as islet cells are not the cell type responsible for endogenous ApoC3 production.…”
Section: Discussioncontrasting
confidence: 99%
“…Our studies are at variance with Avall et al (51), who reported that adenovirus-mediated ectopic ApoC3 production resulted in beta cell apoptosis and dysfunction in MIN6 cells and islets. However, the physiological significance of this study is uncertain, as islet cells are not the cell type responsible for endogenous ApoC3 production.…”
Section: Discussioncontrasting
confidence: 99%
“…This study also reported that apoC-III related to coronary artery calcification in a triglyceride dependent manner Thus, decreasing plasma apoC-III concentrations is able to improve glucose tolerance and help slow disease progression to a certain extent, providing new thinking for treating diabetes besides hypoglycemic drugs (49,50). …”
Section: Accepted Manuscriptmentioning
confidence: 75%
“…Previous data indicated that therapeutic measures, including the use of antisense toward apoC-III mRNA, attenuated its apoptosis effect. Type 2 diabetic insulin resistance, partly attributed to hypertriglyceridemia, could be caused by high levels of apoC-III, which further accelerates the intra-islet apoptosis process (50). In a study conducted by Omar's group, they found that plasma apoC-III levels were correlated positively with fasting glucose and hemoglobin A1c (HbA1c) in type 2 diabetic patients (51).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Furthermore, insulin resistance can also increase the production of other proteins such as apoCIII which affect or influence the circulating levels of lipoprotein. ApoCIII is a small apoprotein that may increase VLDL and LDL-C by preventing the action of lipoprotein lipase (LpL) and inhibiting lipoprotein uptake via the LDL receptor-related protein [16]. Another possible factor for the pathogenesis of diabetic dyslipidemia is the hepatic lipase deficiency which results from insulin resistance or relative insulin deficiency.…”
Section: Introductionmentioning
confidence: 99%